Corporate governance and real earnings management: evidence from Indonesian fraudulent and non-fraudulent listed companies / Yuztitya Asmaranti, Norziana Lokman and Rahayu Abdul Rahman - Asmaranti, Yuztitya; Lokman, Norziana; Abdul Rahman, Rahayu (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2024)
Corporate governance mechanisms provide a framework to mitigate managerial misbehaviour, including the manipulation of earnings. Despite their intended functions, the persistence of earnings management practices remains, ultimately contributing to instances of financial reporting fraud. Thus, this study aimed to examine how corporate governance attributes may affect the occurrence of earnings management, in particular real earnings management among Indonesian fraudulent and non-fraudulent listed companies. Using 192 firm-year observations, in the span of 2012-2021, the findings showed that educational background of the board of commissioners and board of directors significantly affected real earnings management practices. Nevertheless, this study failed to find a significant relationship between real earnings management and other corporate governance attributes, including changes in the board of commissioners (BOC), changes in the board of directors (BOD), the independence of BOC, the size of the audit committee, and the occurrence of auditor change. The findings of this study provide preliminary evidence on the importance of board education to influence real earnings management practices.